1879 Ind. Acts 210 - (:unkn) unknown (My University, 1879)
An Act To Amend the Thirtieth Section of an Act Entitled "An Act Granting The Citizens Of The Town Of Evansville, In The County Of Vanderburgh," pt. 9: Granted the city council the authority to regulate the keeping and conveying of gunpowder and all other combustible and dangerous materials, including the use of candles and lights in barnes and stables.
Keywords: GUNPOWDER - STORAGE